(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-1-234-247 The article examines the speeches of the outstanding Don publicist Viktor Sevsky in the satirical magazines “Beach”, “Drum”, “New Satyricon” in 1917. The study reveals the problem-thematic and genre characteristics of V. Sevsky’s journalism in the context of the development of Russian satirical journalism of the revolutionary period. The dynamics is analyzed how the nature of the journalist’s publications changed throughout 1917: from an ironic assessment of certain aspects of the work of the Provisional Government to sarcastic ridicule of the new government, bureaucracy and speculation. The author presents the main antiheroes of V. Sevsky’s satirical journalism, analyzes the techniques of creating satirical images. Key words: Victor Sevsky, “Beach”, “Drum”, “New Satiricon”, satirical journalism, satirical magazines